Selective harvesting and life history variability of corkwing and goldsinny wrasse in Norway: Implications for management and conservation - Halvorsen, Kim Aleksander Tallaksen (ICES Journal of Marine Science: Journal du Conseil, 2017)
Selective harvesting, where some individuals are actively targeted or possess phenotypes rendering them more vulnerable to capture, is inevitably happening in all commercial and recreational fisheries. Selective harvesting may affect reproduction and recruitment and cause fisheries induced evolution, potentially reducing fisheries yield and resilience to environmental change. Several species of wrasse (Labridae) are now being harvested as cleaner fish to reduce salmon lice-infestations in Norwegian aquaculture. The fisheries are regulated by minimum size limits are presuably sizeselective, but they may also be sex-selective since these wrasses exhibits sexual size dimorphism. In this thesis, I focus on life history traits of corkwing and goldsinny wrasse in the context of a growing, selective fishery in southern Norway. Specifically, my goals were to: 1) Study spatial and sexual variation in life history traits in corkwing (Symphodus melops) and goldsinny wrasse (Ctenolabrus rupestris) and elucidate the underlying processes producing such variation. 2) Estimate size and sex selectivity in the corkwing wrasse fishery and assess the effects of fishing on population parameters of corkwing and goldsinny and 3), evaluate the current management and fishing practice in a selective harvesting perspective. In Paper I, we show that sexual dimorphism of corkwing wrasse is more male biased in populations further north on the western coast of Norway. The size limit is therefore selective against males who builds nests and provide parental care. In Paper II; we further explore the male selective fishery in a tagging experiment, finding that the nesting males have higher vulnerability for being captured in the fishery, independent of body size. It is also shown that a small marine protected area reduces fishing mortality, but have similar sex selectivity as the fished site. In Paper III, we assessed the effect of four MPAs on corkwing and goldsinny populations in Skagerrak, finding that MPAs, relative to control areas, have higher abundance of both species and older and larger corkwing, but no consistent differences for goldsinny. Paper IV further explores goldsinny individual growth rate variability in the same four MPA-control pairs. No MPA effect was detected, but there were indications of growth rates being negatively affected by local population density and abundance of Atlantic cod (Gadus morhua), a wrasse predator. I have shown that the fishery and the current regulations promote selective harvesting of wrasse at different levels which has implications for management. Some specific advices are proposed: For corkwing, introducing a slot size limit (protecting both small and large fish) can protect nesting males and females in more equal proportions. A slot size limit should also be beneficial for goldsinny, which as a considerably longer life span and is therefore more prone for truncated natural age distribution as a consequence of size-selective fishing. Moreover, slot limits are likely to reduce selection for slow growth and ensure a more balanced exploitation of populations with different growth rates. Further, I suggest increasing the number of marine protected areas. The results of paper II and III show that MPAs can be effective as a management tool for wrasse, especially considering that these species exhibit high site fidelity and fine-scaled variability in life history traits.